Thermally Conductive and Shape‐Stabilized Polyethylene Glycol/Carbon Foam Phase‐Change Composites for Thermal Energy Storage. Issue 11 (17th March 2020) - Lin, Fankai; Zhang, Weiyi; Shi, Tengteng; Lv, Zhenfei; Min, Xin; Fang, Minghao; Wu, Xiaowen; Liu, Yan'gai; Huang, Zhaohui
Abstract: Phase‐change materials (PCMs) have been widely investigated as candidates for thermal energy storage and solar thermal energy conversion. However, low thermal conductivity and poor shape stability during phase transition processes are detrimental to their practical applications. In this study, we designed composite PCMs based on carbon foam (CF) via the vacuum impregnation method to overcome these problems. CF with 3D interconnected microporous structures and good compressive strength was fabricated from phenolic resin (PF) using a combined process of carbonization and sacrificial template techniques. The developer material is considered a promising support material for PCMs. The as‐prepared polyethylene glycol/CF composite (PCC) exhibited a high energy‐storage density with a melting enthalpy of 135.7 J/g, and the thermal conductivity was enhanced by 109.8% compared to that of pure polyethylene glycol. In addition, the PCC showed excellent thermal stability and leakage‐proof performance after 100 heating/cooling cycles and good compressive strength. Because of the simple preparation process and low cost, PCC is a promising material for various thermal energy storage applications, especially in building energy storage systems. Abstract : A porous and lightweight carbon foam was prepared based on phenolic resin via an economical polyurethane foam templating technique, which acted well as a perfect supporting material for PEG thermal storage material. The as‐prepared PEG/ carbon foam composite indicated good mechanical performance, large phase‐change latent heat, excellent thermal stability, which demonstrated great potential applications in various thermal energy storage fields, especially in energy‐efficient buildings.